2019
DOI: 10.1177/0954406219883904
|View full text |Cite
|
Sign up to set email alerts
|

A simulation-based study on the effect of underwater friction stir welding process parameters using different evolutionary optimization algorithms

Abstract: This paper investigates the effect of underwater friction stir welding process parameters on the mechanical properties of the aluminum alloy 6082-T6 joint and further simulates this process using various evolutionary optimization algorithms. Three independent underwater friction stir welding process parameters, i.e. shoulder diameter (in mm) at two levels, rotational speed (in r/min) at three levels, and traverse speed (in mm/min) also at three levels, were varied according to the Taguchi’s L18 standard orthog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This empirical model has been solved for maximizing the grade value using PSO within the defined limits of the EDD input parameters. This PSO algorithm (Marini and Walczak, 2015;Wahid et al, 2020) is solved by calculations of the movement of swarms, fish or flocks. The number of generations, population of swarms and upper and lower limits play a pivotal role in the solutions suggested by PSO algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…This empirical model has been solved for maximizing the grade value using PSO within the defined limits of the EDD input parameters. This PSO algorithm (Marini and Walczak, 2015;Wahid et al, 2020) is solved by calculations of the movement of swarms, fish or flocks. The number of generations, population of swarms and upper and lower limits play a pivotal role in the solutions suggested by PSO algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanical properties of the aluminum alloy 6082-T6 joint are influenced by the process parameters of underwater friction stir welding. Various evolutionary optimization approaches are used to describe this process [8]. Electron backscatter diffraction technique was utilized to analyze microstructural changes and texture evolution in different 7003/6060 aluminum alloys during underwater friction stir welding [9] Microstructural analysis showed that most fractures are located in the thermomechanically damaged zone [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the estimation results obtained, they reached data close to the results obtained from the experimental studies with very low error rates. Wahid et al 24 have benefited from hybrid artificial intelligence techniques in underwater friction stir welding process. In the created prediction model, shoulder diameter, rotation speed, rotation speed were selected as input parameters, while some mechanical properties of 6082-T6 aluminum alloy were selected as output values.…”
Section: Introductionmentioning
confidence: 99%